The influence of content marketing and destination branding on consumer preferences at garland barnville - Arifah, Inara Hilmi; Ramdhani, Abdullah; Muharam, Husni (Institute of Computer Science (IOCS), 2025)
This study investigates the influence of content marketing and destination branding on consumer preferences at Garland Barnville, a Swiss-themed cafe in Garut. Using a quantitative approach with PLS-SEM on 100 respondents, findings reveal that both content marketing (? = 0.524; p < 0.05) and destination branding (? = 0.391; p < 0.05) significantly and positively affect consumer preferences, with an overall explanatory power of 75.4%. These results indicate that consumer attraction shaped not only by product quality but also by visual narratives and destination identity, thereby reinforcing the relevance of the “experience economy” perspective. Theoretically, this study contributes to the literature by extending destination branding and content marketing research into the thematic cafe sector, an area underexplored compared to mainstream tourism. Practically, the findings provide implications for managers, emphasizing the need to balance aesthetic storytelling with core product quality to ensure sustainable competitiveness and repeat visits